(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Populations of the species Scolytus mali distributed in the Fergana Valley living on apple and apricot trees were comparatively analyzed, and the indicators of variability of morphometric characters between one population and the similarities and differences of morphometric characters between populations and between species at the 1% level of significance (P <0.01) proved to be.